Pricing-to-Market and Exchange Rate Pass-Through Analysis of Sri Lankan Desiccated Coconut Export Markets - Maria Dorin, M.; Sooriyakumar, K (University of Jaffna, 2016)
This article analyses the pricing to market strategy for Sri Lankan desiccated coconut export market. Market fluctuation in the value of the Sri Lankan Rupees can alter the prices of exported goods in terms of foreign currencies. Therefore, it leads to the Sri Lankan products either more or less expensive or cheaper to foreign buyers and consequently affecting export demand. Therefore, it is threatening to keep steady international export market for Sri Lankan desiccated coconut and to take the production decision when demand frequently fluctuates. The analysis of pricing-to-market (PTM) effects is therefore an important element in assessing the relationship of exchange rate and export prices of tradable goods. A within model is used to analyze the short-run pricing-to-market and between model is used to analyze the long-run pricing-to market. Both models of panel regression is used for analyse the exchange rate pass through of Sri Lankan desiccated coconut in the world market. Seven export market destinations were selected for analysis. This study, investigated the effects of exchange rate volatility on export market price of Sri Lankan desiccated coconut during the period 2003-2014 and viability of expanding the Sri Lankan desiccated coconut market in future. The results (Coefficient) indicate that the complete exchange rate pass through occurs in the export market of desiccated coconut in Sri Lanka in the short-run. 1% of depreciation of Sri Lankan currency in terms of foreign currency units causes to downward the export market prices of desiccated coconut by 2%. These results clearly imply that the short-run pricing-to market is a strategically viable plan to expand the Sri Lankan desiccated coconut market via exchange rate pass through.
Keywords: Between regressions; Desiccated coconut export; Pricing-to-market; Within regression